Redescription of Lemuricola (Madoxyuris) bauchoti (Nematoda, Oxyuridae) from Lemur catta in Madagascar - Robles, Maria del Rosario (2010)
Lemuricola (Madoxyuris) bauchoti Chabaud, Brygoo et Petter, 1965 is redescribed from material collected from the ring-tailed lemur, Lemur catta, from the Beza Mahafaly Special Reserve in Madagascar using the scanning electron microscope. This is a new host record and the first oxyurid reported from the ring-tailed lemur. Previously, records of each species of the subgenus Madoxyuris have been restricted to a single host species, but the close relationship between these nematodes and their Strepsirrhini hosts will only be proven when additional records fill in the gaps in their distribution.